Water Quality Assessment of Anchar Lake, Srinagar, India - Ashraf, Samiyah; Kaur, Simarjot; Singla, Sandeep (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this study was to ascertain the current condition of the Anchar lake water body in the Indian state of J&K in terms of water quality using some main parameters such as pH, TDS, EC, DO, and nitrates content. For the years 2019 and 2020, samples were obtained for two seasons: summer and winter.
Keywords: water quality; Anchar lake; TDS; pH; sewage; indices; jakość wody; jezioro Anchar; ścieki